1985
DOI: 10.1002/cne.902420310
|View full text |Cite
|
Sign up to set email alerts
|

Cortical and subcortical afferent connections of the primate's temporal pole: A study of rhesus monkeys, squirrel monkeys, and marmosets

Abstract: The afferent connections of the primate's temporopolar cortex were investigated with the retrograde horseradish peroxidase technique. Old World and New World monkeys received small unilateral injections of horseradish peroxidase. These labeled cells in a number of cortical, thalamic, and brainstem regions and in a few further telencephalic and diencephalic regions. Cortically, the neighboring areas of the inferior and superior temporal gyrus and the insula contained a considerable number of labeled cells. Furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
95
0
2

Year Published

1991
1991
2012
2012

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 171 publications
(109 citation statements)
references
References 91 publications
12
95
0
2
Order By: Relevance
“…The concentration of cells in PM was mainly in the medial portion, which has been associated with auditory cortex Jacobson, 1975, 1976;Romanski et al, 1997;Hackett et al, 1998b). The strong connections between PM and the parabelt are consistent with the position of the parabelt as a later stage in the hierarchy of auditory cortex (Hackett, 2011) as often claimed for higher order areas which receive strong pulvinar inputs (DeVito and Simmons, 1976;Markowitsch et al, 1985;Yeterian and Pandya, 1989;Schmamann and Pandya, 1990;Cusick et al, 1993). The strong links between the pulvinar and parabelt may also indicate that the parabelt is involved in the proposed corticothalamocortical (CTC) circuits that serve to relay information between cortical areas (Sherman and Guillery, 2001;Guillery and Sherman, 2002;Sherman and Guillery, 2002;Sherman, 2007).…”
Section: Regional Comparison Of the Lateral Belt And The Parabeltmentioning
confidence: 54%
“…The concentration of cells in PM was mainly in the medial portion, which has been associated with auditory cortex Jacobson, 1975, 1976;Romanski et al, 1997;Hackett et al, 1998b). The strong connections between PM and the parabelt are consistent with the position of the parabelt as a later stage in the hierarchy of auditory cortex (Hackett, 2011) as often claimed for higher order areas which receive strong pulvinar inputs (DeVito and Simmons, 1976;Markowitsch et al, 1985;Yeterian and Pandya, 1989;Schmamann and Pandya, 1990;Cusick et al, 1993). The strong links between the pulvinar and parabelt may also indicate that the parabelt is involved in the proposed corticothalamocortical (CTC) circuits that serve to relay information between cortical areas (Sherman and Guillery, 2001;Guillery and Sherman, 2002;Sherman and Guillery, 2002;Sherman, 2007).…”
Section: Regional Comparison Of the Lateral Belt And The Parabeltmentioning
confidence: 54%
“…Other lesion studies implicate the left anterior thalamus [Cohen et al, 1994, Moreaud et al, 1995Semenza and Zettin, 1988;Luchelli and De Renzi, 1992]. Tracer studies in nonhuman primates have identified parts of the medial dorsal and pulvinar nuclei as connected to BA 38 [Trojanowski and Jacobson, 1974;Markowitsch et al, 1985;Gower, 1989]. It is possible that the lesions in those studies affected the interaction of anterior temporal cortex with thalamic nuclei.…”
Section: Discussionmentioning
confidence: 99%
“…Additional support to this hypothesis is provided by clinical observations of retrograde amnesia in patients with combined damage of anterolateral temporal areas and prefrontal areas (Markowitsch, 1995b), suggesting that the prefrontal cortex acts as a kind of control center for effortful initiation of recall (Jetter et al, 1986) and the sequencing and organizing of information (Milner et al, 1985;Goldman-Rakic and Friedman, 1991;Stuss et al, 1994;GoldmanRakic, 1995). This, together with the anterolateral temporal cortex which provides a connecting link to posterior cortical centers of integration as the major storage places of engrams (Markowitsch et al, 1985), implies an important role of the prefrontal cortex in the initiation of directed ecphory. The results on prefrontal activation obtained in the present study are in good agreement with the above ideas, because the prefrontal cortex is activated during the ecphory of autobiographical memory retrieval.…”
Section: Prefrontal Cortexmentioning
confidence: 98%